Profil Keterampilan Metakognitif Siswa dalam Menyelesaikan Soal Asesmen Kompetensi Minimum (AKM) Ditinjau dari Kemampuan Matematika - Maidah, Maidah; Ekawati, Rooselyna (MATHEdunesa, 2025)
Metacognitive skills are a person's ability to control their thinking when planning, monitoring, and evaluating their cognitive processes. Students' metacognitive skills that appear when completing minimum competency assessment questions tend to be incomplete. In this case, students need the right strategies to solve these questions. Each student has different thinking processes and problem-solving strategies. One possible cause of this is different levels of mathematical ability. This research is a qualitative research with tests and interview methods that aim to describe students' metacognitive skills in solving AKM problems based on their level of mathematics ability. The subjects of this study were students with high, medium, and low mathematical abilities. Based on the study's results, all indicators of metacognitive skills, ie, planning, monitoring, and evaluation, appeared in subjects with high mathematics ability at every stage of problem solving. Meanwhile, some indicators do not appear completely for students with medium and low mathematics abilities. At the stage of carrying out the plan, the evaluation component was the indicator of metacognitive skills that did not appear in low-ability students. Meanwhile, for students with low mathematics ability, the indicators that did not appear were planning and monitoring in the stages of devising a plan and carrying out the plan.